2007
DOI: 10.1111/j.1365-2958.2007.05827.x
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved transcriptional repressor controls a large regulon involved in lipid degradation in Mycobacterium smegmatis and Mycobacterium tuberculosis

Abstract: SummaryThe Mycobacterium tuberculosis TetR-type regulator Rv3574 has been implicated in pathogenesis as it is induced in vivo, and genome-wide essentiality studies show it is required for infection. As the gene is highly conserved in the mycobacteria, we deleted the Rv3574 orthologue in Mycobacterium smegmatis (MSMEG_6042) and used real-time quantitative polymerase chain reaction and microarray analyses to show that it represses the transcription both of itself and of a large number of genes involved in lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
274
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(286 citation statements)
references
References 60 publications
9
274
0
2
Order By: Relevance
“…Ksh1 (KshA1B1), Ksh2 (KshA2B2), Ksh3 (KshA1B2), Ksh4 (KshA2B1). However, a detailed analysis of the upstream sequences of these genes showed that only the MSMEG_5925 ( kshA1 ) and MSMEG_6039 ( kshB1 ) genes are preceded by promoters inducible by cholesterol, having the consensus operator sequence for the binding of the KstR repressor, one of the regulators of cholesterol catabolism (named KstR regulon) (Kendall et al ., 2007). Moreover, microarray expression experiments carried out on M. smegmatis indicate that kshA1 and kshB1 are induced 1.9‐fold and 7.0‐fold, respectively, in cholesterol with respect to glycerol (Table 1) (UhĂ­a et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Ksh1 (KshA1B1), Ksh2 (KshA2B2), Ksh3 (KshA1B2), Ksh4 (KshA2B1). However, a detailed analysis of the upstream sequences of these genes showed that only the MSMEG_5925 ( kshA1 ) and MSMEG_6039 ( kshB1 ) genes are preceded by promoters inducible by cholesterol, having the consensus operator sequence for the binding of the KstR repressor, one of the regulators of cholesterol catabolism (named KstR regulon) (Kendall et al ., 2007). Moreover, microarray expression experiments carried out on M. smegmatis indicate that kshA1 and kshB1 are induced 1.9‐fold and 7.0‐fold, respectively, in cholesterol with respect to glycerol (Table 1) (UhĂ­a et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the relevant role that the kstR regulon seems to play, the mechanisms involved in this regulation are still poorly understood. Gel retardation assays have shown that KstR binds as a dimer to DNA probes containing an in silico-identified motif (TNNAACNNGTTNNA) (Kendall et al, 2007). However, experimental evidence that this motif represents the authentic KstR operator remains to be presented.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent biochemical and structural studies have assigned a role for some of the mycobacterial genes in cholesterol catabolism, the complete degradative pathway and its specific regulation remain to be fully established (Capyk et al, 2009;Knol et al, 2008;Lack et al, 2010;Yam et al, 2009). Recently, it has been shown that cholesterol utilization in mycobacteria is controlled by two TetR-type transcriptional repressors (Kendall et al, 2007(Kendall et al, , 2010. One of these repressors, named KstR, is encoded by the Rv3574 gene in M. tuberculosis and by the MSMEG_6042 gene in M. smegmatis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rv3334 is a member of the MerR family of transcriptional regulators, and a recent study has found that Rv3334 is an auto repressor but positively regulates the expression of kstR , which encodes a transcription factor [35]. Cholesterol catabolism is essential for M. tb persistence [36,37] and KstR controls a large regulon mediating cholesterol degradation and lipid metabolism [36]. As such, Rv3334 may play an active role in the response of M. tb to hypoxia.…”
Section: Resultsmentioning
confidence: 99%